2008
DOI: 10.1149/1.2897758
|View full text |Cite
|
Sign up to set email alerts
|

Proton Conduction in Sn[sub 0.95]Al[sub 0.05]P[sub 2]O[sub 7]–PBI–PTFE Composite Membrane

Abstract: Proton-conducting composite membranes were fabricated by blending Sn 0.95 Al 0.05 P 2 O 7 having an excess of phosphates with polybenzimidazole ͑PBI͒ and polytetrafluoroethylene ͑PTFE͒. The addition of PBI to Sn 0.95 Al 0.05 P 2 O 7 -P x O y powder stabilized the conductivity of the composite, providing higher conductivities than those of stoichiometric Sn 0.95 Al 0.05 P 2 O 7 . The addition of PTFE to Sn 0.95 Al 0.05 P 2 O 7 -P x O y -PBI powder reduced the conductivity but increased the tensile strength. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…However, limited information is available even for the most extensively studied SnP 2 O 7 -based systems. Heo et al 10 reported a 50% decrease in conductivity for Sn 0.95 Al 0.05 P 2 O 7 -P 0.6 O 2.1 after being kept in a dry atmosphere for 10 h, whereas Xu et al 33 reported a higher stability for the SnP 2 O 7 -H 3 PO 4 system. These results are also included in Fig.…”
Section: Conductivity Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, limited information is available even for the most extensively studied SnP 2 O 7 -based systems. Heo et al 10 reported a 50% decrease in conductivity for Sn 0.95 Al 0.05 P 2 O 7 -P 0.6 O 2.1 after being kept in a dry atmosphere for 10 h, whereas Xu et al 33 reported a higher stability for the SnP 2 O 7 -H 3 PO 4 system. These results are also included in Fig.…”
Section: Conductivity Stabilitymentioning
confidence: 99%
“…Great efforts are being made to develop new proton conducting materials as electrolytes for fuel cells operational at intermediate temperatures from 200 to 400 C. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] This temperature range is of strategic importance, since it bridges the gap between the currently available high and low temperature fuel cells. A number of biofuels can be directly oxidized or reformed to hydrogen via an internal reformer in this temperature range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is done to avoid the high acid loadings required to achieve reasonable conductivity which can cause mechanical stability issues with the PBI membranes [66][67][68]. An avenue to avoid this issue currently being researched involves filling the membrane with solid proton conductors such as solid acids, ionic liquids, and graphite [50,[69][70][71][72][73][74][75][76][77][78] or hygroscopic materials [79][80][81][82].…”
Section: High Temperature Polymer Electrolyte Membranesmentioning
confidence: 99%
“…Area-specific resistance of pellet-form electrolytes is very high, hindering their application in ITFCs [15]. Hibino et al reported several works on the topic of inorganic/organic composite electrolytes using metal phosphates as the proton conductor for ITFCs [7,[19][20][21][22]. By adding organic binders, they prepared Sn0.9In0.1P2O7 composite membranes with a thickness of less than 150 μm, having a relatively low ASR of 0.24 Ω cm 2 [7].…”
Section: ×10mentioning
confidence: 99%